Pancreatic Colloid Carcinoma in an Elderly Cat. Issue 4 (November 2017) - Hagiwara, K.; Michishita, M.; Yoshimura, H.; Ochiai, K.; Azakami, D.; Ishiwata, T.; Takahashi, K.
Summary: A 21-year-old neutered female domestic shorthaired cat was presented with a history of inappetence, vomiting and haematuria. The cat was humanely destroyed at the owner's request and a necropsy examination was performed. A 0.8 × 0.5 × 0.5 cm mass was located in the left lobe of the pancreas. The mass was gelatinous in nature and the external and cut surfaces were pale yellow in colour. Microscopically, the mass was non-capsulated and comprised an accumulation of extracellular stromal mucin containing suspended neoplastic columnar epithelial cells forming tubular structures. Immunohistochemically, these cells diffusely expressed cytokeratin (CK) AE1/AE3, CK7 and carcinoembryonic antigen and were partially positive for CK19 and trypsin, but negative for vimentin. The tumour was diagnosed as a colloid carcinoma. The clinical presentation in this case was caused by chronic renal failure complicated by secondary renal hyperparathyroidism and associated metastatic calcinosis. To the best of our knowledge, this is the first report of colloid carcinoma arising from the pancreas in a cat.